2006
DOI: 10.1093/jxb/erl138
|View full text |Cite
|
Sign up to set email alerts
|

The apoplastic antioxidant system in Prunus: response to long-term plum pox virus infection

Abstract: This work describes, for the first time, the changes taking place in the antioxidative system of the leaf apoplast in response to plum pox virus (PPV) in different Prunus species showing different susceptibilities to PPV. The presence of p-hydroxymercuribenzoic acid (pHMB)-sensitive ascorbate peroxidase (APX) (class I APX) and pHMB-insensitive APX (class III APX), superoxide dismutase (SOD), peroxidase (POX), NADH-POX, and polyphenoloxidase (PPO) was described in the apoplast from both peach and apricot leaves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
144
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(157 citation statements)
references
References 44 publications
9
144
0
1
Order By: Relevance
“…4a). This result is in accordance with the results of Tobacco mosaic virus infected tobacco (Lagrimini and Rothstein,1987), plum pox virus infected peaches, apricots (Diaz-Vivancos et al, 2006), Beans yellow mosaic virus infected beans (Radwan et al, 2010), Potato virus Y infected potato (Milavec et al, 2001), tomato and bell pepper infected with Tobacco mosaic virus and Tomato mosaic tobamo virus (Madhusudhan et al, 2009), Cucumber mosaic virus and Zucchini yellow mosaic virus infected Cucumis sativus and Cucurbita pepo plants ( Riedle-Bauer, 2000), Tobacco mosaic virus infected tobacco plants (Kiraly et al, 2002), Tomato yellow leaf curl virus infected tomato plants (Dieng et al, 2011), Banana bunchy top virus infected cultivars of banana (Devanathan et al, 2005), geminivirus infected Capsicum annum (Meena et al, 2008) and cotton with CLCuBuV (Siddique et al, 2014). Virus infection appears to stimulate POX activity in all hosts in (Wood, 1990).…”
Section: Total Phenolsupporting
confidence: 92%
“…4a). This result is in accordance with the results of Tobacco mosaic virus infected tobacco (Lagrimini and Rothstein,1987), plum pox virus infected peaches, apricots (Diaz-Vivancos et al, 2006), Beans yellow mosaic virus infected beans (Radwan et al, 2010), Potato virus Y infected potato (Milavec et al, 2001), tomato and bell pepper infected with Tobacco mosaic virus and Tomato mosaic tobamo virus (Madhusudhan et al, 2009), Cucumber mosaic virus and Zucchini yellow mosaic virus infected Cucumis sativus and Cucurbita pepo plants ( Riedle-Bauer, 2000), Tobacco mosaic virus infected tobacco plants (Kiraly et al, 2002), Tomato yellow leaf curl virus infected tomato plants (Dieng et al, 2011), Banana bunchy top virus infected cultivars of banana (Devanathan et al, 2005), geminivirus infected Capsicum annum (Meena et al, 2008) and cotton with CLCuBuV (Siddique et al, 2014). Virus infection appears to stimulate POX activity in all hosts in (Wood, 1990).…”
Section: Total Phenolsupporting
confidence: 92%
“…Minor changes in the activity of enzymes, lipid peroxidation, and hydrogen peroxide content were found in susceptible hosts (Madhusudhan et al 2009). Long-term infection by plum pox virus studied by Díaz-Vivancos et al (2006) in peach and apricot showed that general increase in H 2 O 2 concentration led to lipid hydroperoxidation of cell membranes and proteins in susceptible, but not in resistant hosts. In compatible interactions, ion leakage, a marker of damaged plasmalemma, was accompanied by a decrease in POX and superoxide dismutase activity, whereas in the incompatible interactions, the activities of these enzymes were increased.…”
Section: Discussionmentioning
confidence: 99%
“…The variation in the level of reactive nitrogen and oxygen species (RONS) is viewed as a common feature of biotic stress and is observed both in compatible and incompatible plant-virus interactions (Hinrichs-Berger 1999;Díaz-Vivancos 2006). RONS act as signalling molecules as well as effectors of programmed cell death, which is involved in plant resistance (Lamotte 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The peroxidases belonging to PCOX superfamily exclusively contain animal peroxidases which have been suggested to be involved in the innate immunity, defense responses etc. [4]. The myeloperoxidase, eosinophil peroxidase, lactoperoxidase, etc.…”
Section: Introductionmentioning
confidence: 99%